Por uma teoria crítica da cisgeneridade: enquadramentos e rupturas do olhar no documentário brasileiro - Soares, Aline Rebouças Azevedo (2024)
The research studies the aesthetic intersection of cisgenderity in Brazilian documentaries, based on the analysis of five works that make up the corpus: Katia, o filme (2012), O voo da beleza (2012), Meu corpo é politico (2017), Bixa Travesty (2018) and Lembro mais dos corvos (2018). Each of them features one or more biographical narratives of trans people. The selection especially the year of release of the work (from 2010 onwards) and the involvement of trans people in the production. I started from a reflection on the contemporary sociopolitical scenario in Brazil based on authors from Critical Social Psychology, in which it was possible to observe positions of intolerance towards gender diversity and other social groups considered minorities, in addition to “flirtations” with authoritarian modes of public management , especially after the 2018 presidential elections. I work with the term cisgenderness according to Viviane Simakawa, who, in addition to identifying oneself with the gender assigned at birth, states that it is a concept formed by Westernized sociocultural understandings of gender, which are disseminated and perpetuated as natural and biological. For the author, cisgenderness needs to be thought of as a practice that crosses and relates colonial gender projects and modern racist projects. The methodology is guided by the primacy of the object according to Adorno, and articulates immanent discourse analysis, film analysis, Walter Benjamin's concepts of constellation, and the conception of montage-gem, according to Aby Warburg. The analyzes indicated emancipatory potential in these works and some aesthetic choices that can be considered subversive to the classic modes of filming. On the other hand, the majority participation of people in these productions points to the crossing of cisgenderity in the construction of the gaze, which has also been evident in the filmic form of each of these documentaries. I believe that reflections on the intersections of cisgenderness in the construction of the gaze – from the camera's gaze –, as well as the elaboration of a methodological path aimed at analyzing audiovisual productions, could contribute to research in Critical Social Psychology and related areas that come to work - look with corpus of this type. They can also point out the urgency of elaborating and discussing a Brazilian critical theory of cisgenderity and, consequently, of other possibilities for producing a view.